Estimation of leaf photosynthetic capacity from the photochemical reflectance index and leaf pigments. (March 2020) - Chou, Shuren; Chen, Bin; Chen, Jing; Wang, Miaomiao; Wang, Shaoqiang; Croft, Holly; Shi, Qin
Highlights: ChlaLeaf *CarLeaf is found to be highly correlated with Vcmax25 . PRILeaf _noon is also found to be highly correlated with Vcmax25 . PRILeaf_noon *(ChlLeaf + CarLeaf ) is found to be highly correlated with Vcmax25 . Abstract: Leaf chlorophyll content has recently been found to be a better proxy than leaf nitrogen content for leaf photosynthetic capacity in a mixed deciduous broadleaf forest. A key concept underlying the relationship between leaf photosynthetic capacity and leaf chlorophyll content was the coordinate regulation of photosynthetic components (i.e. light harvesting, photochemical, and biochemical components). In order to test this hypothesis, we measured seasonal variations in leaf nitrogen content (Nleaf ), leaf photosynthetic pigments (i.e. chlorophyll (ChlLeaf ), carotenoids (CarLeaf ) and xanthophyll (XanLeaf )) and leaf photosynthetic capacity (i.e. the maximum rate at which ribulose bisphosphate (RuBP) is carboxylated (Vcmax25 ) and regenerated (Jmax25 ) at 25 °C) at a paddy rice site during the growing season in 2016. We investigated the effectiveness of (Nleaf ), leaf photosynthetic pigments, leaf-level photochemical reflectance index at sunny noon (PRILeaf_noon ) and their possible combinations for estimating leaf photosynthetic capacities (i.e. Vcmax25 and Jmax25 ) at a paddy rice site. ChlLeaf was highly correlated to Vcmax25 and Jmax25 (R 2 = 0.89 and 0.87, respectively), which were better than Nleaf (R 2 = 0.80 and 0.85, respectively). The products of PRILeaf_noon with leaf pigments (i.e. ChlLeaf, CarLeaf and XanLeaf ) were also found to be highly correlated with Vcmax25 (R 2 = 0.95–0.96). Also, the product of leaf chlorophyll a and CarLeaf was a good proxy for Vcmax25 (R 2 = 0.93). In sum, this study supported the previously findings that leaf chlorophyll content was better correlated with Vcmax25 than leaf nitrogen content. Also, combining PRILeaf_noon with leaf pigments (i.e. ChlLeaf, CarLeaf and XanLeaf ) offered an additional way to estimate leaf photosynthetic capacity (i.e. Vcmax25 ). These findings supported the hypothesis of coordinate regulation of photosynthetic components and they would be helpful to estimation of leaf photosynthetic capacity using remote sensing data.